2013
DOI: 10.1002/adsc.201300439
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structures of Air‐Stable Binuclear Hafnocene Perfluorobutanesulfonate and Perfluorobenzenesulfonate and their Catalytic Application in CC Bond‐Forming Reactions

Abstract: The two air‐stable μ2‐hydroxy‐bridged binuclear hafnocene perfluorobutanesulfonate and perfluorobenzenesulfonate complexes were successfully synthesized. The high catalytic activity and recyclability of these complexes were exemplified for various carbon‐carbon bond formation reactions. Compared with our previously reported hafnocene perfluorooctanesulfonate, these complexes show stronger Lewis acidity and better catalytic activity, and should find broad applications in organic synthesis.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…2,[16][17][18][19][20][21][22] In addition, the use of protic acids has been explored to a lesser extent [23][24][25][26][27] Tetravalent metal complexes with fluoroalkylsulfonate ligands constitute an interesting class of water-stable Lewis acidic catalysts for a variety of transformations. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Despite this, this catalyst class is hardly represented in the context of dehydrative substitution of alcohols in contrast to its trivalent (and bivalent) counterparts. [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] In direct etherification, two alcohols are joined with loss of water.…”
Section: Introductionmentioning
confidence: 99%
“…2,[16][17][18][19][20][21][22] In addition, the use of protic acids has been explored to a lesser extent [23][24][25][26][27] Tetravalent metal complexes with fluoroalkylsulfonate ligands constitute an interesting class of water-stable Lewis acidic catalysts for a variety of transformations. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Despite this, this catalyst class is hardly represented in the context of dehydrative substitution of alcohols in contrast to its trivalent (and bivalent) counterparts. [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] In direct etherification, two alcohols are joined with loss of water.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction proceeded smoothly as expected. However, the product 1 thus obtained was very difficult to purify because of the similar polarity of ketone 1 and the side product (which later was proven to be the known dione 18 ). In comparison, the polarity difference observed between the components of crude 7 was much larger.…”
Section: Resultsmentioning
confidence: 99%
“…29 These water-tolerant perfluorooctanesulfonate catalysts were determined to have a Lewis acidity similar to that of Sc(OTf) 3 , 30 and demonstrated a similar ability to catalyze transformations such aldol reactions, acylations, amidations, glycosylations, and esterifications. 14,[29][30][31][32][33][34][35][36] In addition, these perfluoroalkylsulfonate complexes could be recycled up to five times in Mannich reactions, allylations and aldol reactions, 30 similar to rare-earth metal triflate complexes. However, despite the efficiency of the reported protocols, the use of long-chain perfluorinated sulfonates raises concerns due to toxicity and bioaccumulative properties, 37,38 and these substances have been classified under REACH with restricted use as result.…”
Section: Synpacts Synlettmentioning
confidence: 99%
“…[6][7][8][9][10] In addition, triflate and longer-chain perfluoroalkylsulfonate complexes of, for example, Bi and Ga have been found to be water-tolerant. [11][12][13][14][15][16] As a common feature, it has been suggested that the metal triflate complexes are activated by water, which induces a dissociation of the counterions from the central Lewis acidic metal ion, thereby allowing for Lewis bases to coordinate. 17 Triflate complexes based on group IV metals are considerably less explored compared to their counterparts of lower valency.…”
mentioning
confidence: 99%